Evaluation of Jatigede Reservoir water quality parameters to support fisheries ecosystems - Marsela, Kristina; Dhea, Luthfia Ayu; Hidayah, Lisa Nur; Adhihapsari, Wirastika; Aida, Gilang Rusrita (Universitas Malikussaleh, 2025)
Jatigede Reservoir is one of the multi-functional reservoirs located in Sumedang Regency, West Java, Indonesia. The utilization of Jatigede Reservoir by the community caused ecological pressures that have resulted in a decrease in water quality and fisheries sustainability. The purpose of this study was to evaluate water quality parameters in Jatigede Reservoir to support a sustainable fisheries ecosystem. Sampling was done using purposive sampling and analysis using comparative descriptive. The results showed that the water temperature ranged from 26-29oC, pH 7.9-8.4, and dissolved oxygen 4-5.3 mg/L which still supports fisheries activities. The parameters of light transparency ranged from 0.19-1.1 m, total phosphorus 0.047 - 0.161, and chlorophyll-a 11 - 116 mg/m3 which exceeded the established quality standards. So it is necessary to manage and control pollution in Jatigede Reservoir to improve water quality and support the sustainability of the fisheries ecosystem. Keywords: Fisheries Ecosystem; Jatigede Reservoir; Water Quality